Impact of Silver Barb (Barbodes Gonionotus) Rearing on the Benthic Community and Nutrient Levels of Rice Fields at Sg. Manik, Teluk Intan, Perak, Malaysia - Chamraun, Sun (2006)
The aims of this study are to investigate the impact of silver barb fishes (Barbodes gonionotus) reared in rice field on the benthic organisms and also its impact onto nutrients level in water, sediment and paddy plant in rice field. The study was carried out at Sungai Manik ricefields, where rice was cultivated in the main and off seasons. Rice was planted by direct casting with paddy variety MR 219 at the sowing rate of 80 kg/ha. The experiments were performed in three growing seasons (July - November 2003, February - June 2004 and July - November 2004). The experimental plot was divided into subplots measuring 15 x 20 m and partitioned using corrugated zinc sheets. The field was fully flooded two weeks after planting. The water level in the field was maintained at about 20 cm. A trench of about 1 m in depth and about 1 meter in width was dug along the periphery of the plot and water is allowed to flow freely by connecting 4" PVC pipes that were covered with fine mesh net. Three fingerling densities were introduced into the plots at the rate of 4,000, 8,000 and 12,000 fingerlings/ha at 20 days after rice casting. The range of sizes of fingerlings released were 8.78 ± 0.88 to 11.05 ± 1.58 cm. Three replicates were carried out for each treatment arranged in fully randomized designed. There was no insecticide applied during the growing periods. Herbicide was applied at two weeks before and after sowing. The fish was not given any supplemental food until the harvesting time after 80 days of introduction. Samples of paddy plants, sediments, water and benthic organisms were collected in a stratified random number in six replicates in each treatment at two weeks interval. Benthic organisms were sampled by using core sampler made of PVC pipe of 20 cm in diameter and 500 cm in length. From each treatment, six fishes were taken at 50 days after rice casting for its stomach content analysis. Sampled water was preserved with 2 drops of concentrated hydrochloric acid immediately after sampling. Paddy plants and sediments were dried and weighed before digestion. The paddy plant, sediment and water samples of the last two trials were analyzed for nitrogen-ammonia, phosphorus-phosphate and potassium. The fish harvested ranged from 960 to 1967 (mean 1,317 ± 448) fishes from the plot 4,000 fishes/ha, 1000 to 2600 (mean 1,883 ± 582) fishes from the plot 8,000 fishes/ha and 3934 to 4400 (mean 4,111 ± 252) fishes from the plot 12,000 fishes/ha. The macrobenthic organisms found in the ricefield were mainly from 3 main groups namely gastropods, annelids and insects. Annelid was found to be the dominant group. There was no sign of remaining tissue of any invertebrate found from the stomach examined. The fishes did not consume macrobenthos thus it gave no negative impact on the population of benthic organisms in the ricefield. Nevertheless, it indicated that the oligochaetae worm benefited from the presence of large number of fish in the ricefield. It was thought that the dropping of the fish might contribute to the increased number of worm in the field. Results of nutrient analysis in water showed the ammonia content was in the range of 0.76 to 1.94 mg/litre throughout the growing periods. Statistical analysis showed the concentration of water ammonia did not differ significantly between fish treatments. The soluble phosphate was in the range of 0.007 to 0.022 mg/litre, where the concentrations were high at the early of growing period, but it decreased slightly at the end of growing period. Statistical analysis showed the soluble phosphate in the water differed significantly between fish treatments. The potassium content was in the range of 1.16 to 12.33 mg/litre, the concentrations were higher at the early of growing period, but there was a decreasing trend toward the end of the growing period. However, statistical analysis showed there was no significant different of the potassium content between fish treatments. In the sediment, the total nitrogen content was in the range of 3.70 to 4.68 mg/g DW, the statistical analysis showed there was a significant different between fish treatments only at the 65th day of the growing period. The total phosphorus content in the sediment was in the range of 0.15 to 0.39 mg/g DW. Statistical analysis showed no significant different of phosphorus content between fish treatments. The potassium content in the sediment was in the range of 14.66 to 26.33 mg/g DW, where the statistical analysis showed there was a significant different between fish treatments at the early of growing period. In this study, total nitrogen, total phosphorus and potassium content of the stem and root were analyzed separately. The total nitrogen content in the stem was in the range of 7.22 to 32.04 mg/g DW and 7.57 to 17.50 mg/g DW in the root. The total phosphorus content in the stem was in the range of 0.35 to 2.93 mg/g DW and 0.29 to 2.10 mg/g DW in the root. The potassium content in the stem was in the range of 21.83 to 36.33 mg/g DW and 12.50 to 25.33 mg/g DW in the root throughout the growing periods. The results of statistical analysis showed there was no significant different of the total nitrogen, phosphorus and potassium in the stem and root of paddy plant between plots with fish at difference densities during the growing periods. It is concluded that based on the results of this study, the impact of fish on benthic community and nutrient levels in water, sediment and rice plant were not significant. The feeding behavior of fish introduced, which are not bottoming feeder, have no effect on the community of benthic organisms and it did not also enhance better condition of sediment water interface for a better plant growth.